(untitled) (Journal of Academic Research, 2025)
Background: Brain tumor surgery represents a high-stakes and technically demanding area in neurosurgery. This study aims to systematically analyze the incidence and types of postoperative complications, using data from a tertiary care center, with emphasis on tumor type and surgical context. Methods: This meta-analysis is based on data collected between January 2022 and September 2023 from adult patients who underwent surgery for intracranial tumors. Adverse events (AEs) occurring within 30 days postoperatively were documented by attending neurosurgeons. Tumor histology, surgical approach, urgency, and complications were analyzed. Results: Among 1,173 patients (mean age 57.4 ± 15.3 years), 93.4% underwent elective surgery. The most common tumors were meningiomas (31.1%) and gliomas (28.2%). The rate of surgery-related AEs was 12.7%, with dural leaks observed in 1.5% of cases. Postoperative hemorrhage was a significant issue, especially among glioma patients; 10 experienced bleeding and 8 required reoperations. The 30-day mortality rate was 0.8%, with causes including postoperative bleeding (n=1), pulmonary embolism (n=2), and tumor progression (n=2). Conclusions: Despite the inherent risks associated with brain tumor surgery, the overall mortality in this cohort was low. Comprehensive documentation and early intervention strategies play a crucial role in improving patient outcomes following neurosurgical procedures.